Altered cortical CDC42 signaling pathways in schizophrenia: Implications for dendritic spine deficits - Ide, Masayuki (2010)
BACKGROUND: Spine density on the basilar dendrites of pyramidal neurons is lower in layer 3, but not in layers 5-6, in the dorsolateral prefrontal cortex (DLPFC) of subjects with schizophrenia. The expression of CDC42 (cell division cycle 42), a RhoGTPase which regulates the outgrowth of the actin cytoskeleton and promotes spine formation, is also lower in schizophrenia; however, CDC42 mRNA is lower across layers 3-6, suggesting that other lamina-specific molecular alterations are critical for the spine deficits in the illness. The CDC42 effector proteins 3 and 4 (CDC42EP3, CDC42EP4) are preferentially expressed in DLPFC layers 2 and 3, and CDC42EP3 appears to assemble septin filaments in spine necks. Therefore, alterations in CDC42EP3 could contribute to the lamina-specific spine deficits in schizophrenia. METHODS: We measured transcript levels of CDC42, CDC42EP3, CDC42EP4, their interacting proteins [septins (SEPT2, 3, 5, 6, 7, 8 and 11), anillin], and other spine-specific proteins (spinophilin, PSD-95 and synaptopodin) in the DLPFC from 31 subjects with schizophrenia and matched normal comparison subjects. RESULTS: The expression of CDC42EP3 mRNA was significantly increased by 19.7%, and SEPT7 mRNA was significantly decreased by 6.9% in subjects with schizophrenia. Cortical levels of CDC42EP3 and SEPT7 mRNAs were not altered in monkeys chronically exposed to antipsychotic medications. CONCLUSIONS: Activated CDC42 is thought to transiently disrupt septin filaments in spine necks, allowing the molecular translocations required for synaptic potentiation. Thus, altered CDC42 signaling via CDC42EP3 may perturb synaptic plasticity, and contribute to the spine deficits observed in layer 3 pyramidal neurons in schizophrenia.